A Zn-based coordination compound for fluorescence detection of Fe3+, Cu2+, Ni2+ and CrO42− ions. (1st January 2021) - Han, Li-Juan; Kong, Ya-Jie; Xu, Ya-Yun; Huang, Meng-Meng
Graphical abstract: The multifunctional luminescent probe [Zn(OOCC6 F5 )(H2 O)(C12 H8 N2 )2 ](OOCC6 F5 ) (1 ) has been obtained and it can rapidly detect Fe 3+, Cu 2+, Ni 2+ and CrO4 2− ions with excellent selectivity and sensitivity. Highlights: A zincum coordination compound (1 ) has been obtained. Compound 1 was a multifunctional luminescent probe for detecting Fe 3+, Cu 2+, Ni 2+ and CrO4 2− . Compound 1 has low detection limit and high quenching efficiency. Abstract: Heavy metal ion pollution poses severe risks for human health and the environment, so the development of an effective method for detecting heavy-metal ions remains a serious task. Although fluorescence detection of metal ions has been reported, there are few studies on multifunctional fluorescent probes. In this paper, we synthesized a luminescent coordination compound, [Zn(OOCC6 F5 )(H2 O)(C12 H8 N2 )2 ](OOCC6 F5 ) (1 ), and the fluorescence sensing results exhibited that compound 1 is a multifunctional luminescent probe for detecting Fe 3+, Cu 2+, Ni 2+ and CrO4 2− ions by fluorescence quenching. Luminescence studies demonstrated that compound 1 can rapidly detect Fe 3+, Cu 2+, Ni 2+ and CrO4 2− ions with excellent selectivity and sensitivity, where the quenching efficiencies K sv (Fe 3+ : 4.99 × 10 5  M −1 ; Cu 2+ : 1.50 × 10 5  M −1 ; Ni 2+ : 2.68 × 10 4  M −1 ; CrO4 2− : 2.03 × 10 5  M −1 ) and detection limits (Fe 3+ : 0.240 μM; Cu 2+ : 0.287 μM; Ni 2+ : 0.491 μM; CrO4 2− : 0.388 μM) are regarded as being excellent values for a coordination compound sensor detecting Fe 3+, Cu 2+, Ni 2+ and CrO4 2− ions. We anticipate that a simple and low-cost detection method utilizing compound 1 could be employed to monitor human health and help solve environmental pollution.